Management of Vicharchika Kushta through Ayurveda (AYUSHDHARA, 2024)
Skin disorders in Ayurveda have been mentioned under the broad heading of Kushta. There are 18 types of Kusta which are classified as Maha kushta and Kshudra kushta. Vicharchika is the type of Kshudrakushta. Vicharchika kushta is characterized by symptoms like Kandu, Srava, Pidaka and Shyava varna. Vicharchika is often correlated to eczema based on the clinical presentations. There is no specific treatment or definite cure for Eczema in modern medical science, except some of the symptomatic treatments like application of topical steroid. These steroids cause some serious health hazards like suppression of the hypothalamic pituitary- adrenal axis and even cushingoid features. Whereas Ayurveda has specific treatments like Shodhana and Shamana type of therapies which manages the disease without causing any side effects to the body. In present case report a patient complaints of blackish lesions with itching and discharge since 2 years was treated with Shodhana (Vamana, Virechana) and Shamana aoushadhi, shown a significant results.